On the Variability of the Replacement Investment Capital Stock Ratio: Some Evidence from Capital Scrappage - Bitros, George C.; Kelejian, Harry H. (The Review of Economics and Statistics, 1974)
George C. Bitros, Harry H. Kelejian, On the Variability of the Replacement Investment Capital Stock Ratio: Some Evidence from Capital Scrappage, The Review of Economics and Statistics, Vol. 56, No. 3 (Aug., 1974), pp. 270-278